2020
DOI: 10.3390/ijerph17228592
|View full text |Cite
|
Sign up to set email alerts
|

Livestock Wastewater Treatment in Constructed Wetlands for Agriculture Reuse

Abstract: The aim of this study focused on the evaluation of constructed wetlands (CWs) microcosms, on a laboratory scale, for the removal of metals from a pig industry effluent while maintaining effluent organic matter and nutrients levels for its later used as a fertilizer. CWs with different macrophytes (Phragmites australis and Typha latifolia) and different substrates (light expanded clay aggregate and lava rock) were tested. Results showed high removals of metals during CWs treatment, with removal rates reaching &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Studies suggested that CWs were able to remove organics, total carbon, and nutrients effectively (e.g., fecal indicator bacteria removal ranged from 97% to 99%, such as coliforms and Escherichia coli) [35] but also biological contaminants, metals, or emergent pollutants by more than 85% [36]. In these processes, pollutant removal is reached through a combination of physical, chemical, and biological dynamics and efficiency indicators in which all the elements of CWs (plants, microorganisms, and substrates) can have a significant influence [37], including a positive effect on greenhouse gas emissions reduction [38].…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested that CWs were able to remove organics, total carbon, and nutrients effectively (e.g., fecal indicator bacteria removal ranged from 97% to 99%, such as coliforms and Escherichia coli) [35] but also biological contaminants, metals, or emergent pollutants by more than 85% [36]. In these processes, pollutant removal is reached through a combination of physical, chemical, and biological dynamics and efficiency indicators in which all the elements of CWs (plants, microorganisms, and substrates) can have a significant influence [37], including a positive effect on greenhouse gas emissions reduction [38].…”
Section: Introductionmentioning
confidence: 99%
“…Herbicides were found to be more dominant in the agricultural runoff as it had been found as high as 530 mg/L. The prevalence of other contaminants, such as metals and fungicides, were much lower than the other CECs considered [42,66,68,70].…”
Section: Occurrence Of Pollutants In Agricultural Runoffmentioning
confidence: 94%
“…Studies conducted using the wide range of pollutants and various influent water types (fresh water and saline water) proved that CW microcosm design was adaptable to various wastewater treatments with satisfying removal efficiencies. Their study in 2020 using the same system even achieved toxic metal removal while maintaining the nutrient levels for agriculture reuse [70]. Another study in 2018 using the same system observed removal of organic micropollutants, such as atrazine, clarithromycin, fluoxetine, and norfluoxetine, from the freshwater aquaculture effluents [74].…”
Section: Lab-scalementioning
confidence: 95%
See 1 more Smart Citation
“…Constructed wetlands (CW) are mainly used for sewage treatment of small communities, but there are also applications in industrial wastewaters and leachate of urban waste landfills [27][28][29][30]. In sewage treatment, CW can reduce 84% of total coliform, 96% of FIs, and 89% of EN [31].…”
mentioning
confidence: 99%